Impact of reproductive and sexual health education on late adolescent girls in an urban slum - Verma, Mayuri; Kazi, Yasmeen K. (International Journal Of Community Medicine And Public Health, 2023)
Background: Menstruation, although, a natural process, may result in adverse health outcomes. Adolescents having a better knowledge regarding menstrual hygiene and safe menstrual practices are less vulnerable to reproductive tract infections and its consequences. Aim and Objectives were to study the socio-demographic profile of late adolescent girls in an urban slum. To determine the baseline knowledge of girls regarding reproductive and sexual health and menstrual hygiene. To estimate the impact of reproductive and sexual health education on the existing knowledge. Methods: This study was done among late adolescent girls to assess the impact of health education on their knowledge, attitude and practices regarding menstruation and puberty, conception, contraception, RTI, STI, HIV and AIDS. After collecting sociodemographic details and baseline knowledge, health education session was conducted, which was followed by checking their, post-test knowledge Follow up session was also conducted after a month. Results: Most of the girls were 16 years old, Hindus and from nuclear families. The baseline knowledge about puberty, menstruation, conception, contraception, RTI, STD, HIV, AIDS was not good. The knowledge increased immediately after the first session, but after the second session, the knowledge was not retained. The menstrual hygiene practices increased after the health education session. Conclusions: The study stresses the importance of imparting knowledge about menstruation, hygiene during the periods, to the adolescent girls and having a regular revision session so as to have good menstrual hygiene practices.